Functional Outcomes for Basilar Joint Arthroplasty with Meniscus Allograft Compared with Trapeziectomy Alone. (January 2023) - McCullough, Meghan C.; Minasian, Raquel; Tanabe, Kylie; Rodriguez, Sandra; Kulber, David
Background: Advanced thumb carpometacarpal (CMC) joint arthritis is widely treated with trapeziectomy. To obviate the need for autologous tissue, maintain thumb length, and reduce the risk of scaphoid impingement, the senior author developed an interposition arthroplasty technique using meniscal allograft. We hypothesize that the use of meniscus improves outcomes and subsequent functionality compared with trapeziectomy alone. Methods: Twenty-three patients with Eaton stage III-IV CMC osteoarthritis underwent arthroplasty with meniscal allograft, and 7 patients underwent trapeziectomy alone. Preoperative Disabilities of the Arm, Shoulder, and Hand (DASH), pain, grip and pinch strength, and range of motion scores were compared with postoperative scores at 6 weeks, 6 months, and 1 year. Results: The study group consisted of 17 women and 6 men, and the control group consisted of 5 women and 2 men. The mean age was similar at 61.4 (48-72) years and 65.7 (56-78) years for the study and control groups, respectively. The DASH scores dropped by 61.8% in the study group compared with 38.8% in the control group (<0.01), whereas pain decreased 86.0% and 69.8%, respectively ( P < .01). Strength and range of motion improvement was similar between the groups. Subsidence of the joint space was 1% in the study group compared with 18.4% in the control group. There were no surgical complications in either group. Conclusions: Joint resurfacing with meniscal allograft represents a viable joint salvage option in severe cases of CMC arthritis. Early results suggest that, compared with trapeziectomy alone, the approach results in greater reduction in subjective pain and disability scores, similar improvement in strength measures and range of motion, and less subsidence.